New Approach Needed To Address Declining Forestry Research Capacity And Relevancy in the US: A Call-To-Action - Robert G. Wagner; Alexander L. Friend; Emily J. Silver; Julio Rojas; Thomas R. Fox; Terry Baker; Robert Simpson (Journal of Forestry, 2025)
Recent dramatic reductions in research funding and personnel for university and government organizations by the new federal administration will reduce forestry research capacity in the coming years. However, these cuts only highlight the long-standing decline in forestry research capacity that has been occurring over the past several decades. These reductions will continue to impair the country’s ability to meet the scale and complexity of challenges facing US forests. At some point in the future, there will be an opportunity to rebuild and reshape forestry research capacity to address these challenges. Now is the time to plan the future of forestry research. Successfully rebuilding this capacity will require national support from a broad coalition of forest management organizations. Receiving this support will require substantially increasing the relevancy of research to forest managers relative to what has occurred in recent decades. We offer several suggestions for this rebuilding effort, including: 1) developing a periodic national survey of forest managers to clearly identify the most important problems they face on the ground, 2) regularly communicating results of the survey to forest researchers, program leaders of research funding agencies, policy makers, legislators, and others responsible for allocating forest research effort and funding, and 3) building on the science delivery successes of stakeholder-driven organizations such as the forest manager / university research cooperatives around the country.